Effect of Processing Parameters on Solvent Oil Expression from Loofah Seeds (Luffa cylindrica L.) using Response Surface Methodology - Busari, R. A.; Akpenpuun, T. D.; Iyanda, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Luffah cylindrica plant grows in the wild, around uncompleted buildings and fenced walls. The percentage oil composition of its seeds is about 30% oil. The research focused was the extraction oil from loofah seed using a solvent extraction methodology. Optimum conditions for oil extraction were determined using Response Surface Methodology of Central Composite Rotatable Design. A total of 20 experimental runs were used to investigate the optimum condition considering three independent variables at five levels each: extraction temperature (55, 60, 65, 60, 75ºC), seed/solvent ratio (0.04, 0.05, 0.06, 0.07, 0.08 g/ml) and extraction time (4, 5, 6, 7, 8 hr.). An empirical model equation that could be used to forecast oil yield as a function of the independent variables was developed. The optimum oil yield obtained was 27.43% at the extraction temperature (74.05ºC), seed/solvent ratio (0.05 g/ml) and extraction time (5.35hr). The analysis of variance showed that extraction temperature and time had significant effect on oil yield (p = 0.05). The interaction of the independent variables with oil yield gave R2 and R2 adj. values of 0.98 and 0.93, respectively. The result showed that the selected independent variables had a significant effect on oil yield, thus an optimum condition was established.